Preservation of Spermatozoa Sumba Ongole Bulls Using Citrate Yolk Diluent with the Addition of Palmyra Palm Juice - Anita Tamu Ina; Alexander Kaka (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2020)
The purpose of this study was to determine the quality of the ability of spermatozoa cells to maintain the use of a yolk citrate (YC) diluent with the addition of palmyra palm juice during preservation. The material used for this research was 2 Sumba Ongole bulls as a source of semen. Semen was collected by using an artificial vagina that is processed twice a week. The obtained semen was macroscopically analyzed, including volume, colour, consistency, pH and smell. Meanwhile, microscopic evaluation includes mass movement, motility, concentration, viability and abnormalities. The semen showed >75% motile sperm divided into four treatments and dilute each with YC (P0), 95% YC+5% palmyra palm juice (PPJ) (P1), 90% YC+10% PPJ (P2), 85% YC+15% PPJÂ  and each was stored at 3-50C. The results of statistical analysis showed that P0, P1 treatments were significantly different (P<0.05) between P2, P3 from day 0 to day 4 of storage. The addition of palmyra palm did not affect the motility of spermatozoa, but had a positive effect on the viability of spermatozoa with the addition of 5% palm sap during storage for 4 days at a temperature of 3-5 0C.